Peningkatan Kemampuan Komunikasi Bahasa Arab Calon TKI Berkeahlian Melalui Arabic Camp di Badan Latihan Kerja (BLK) Pondok Pesantren Kebun Baru Palengaan Pamekasan - Gufron Zainal Abidin Sdawi Manasiq (Ulumuna: Jurnal Studi Keilsman, 2023)
The Arabic Camp program is a program organized by BLK Ponpes. Kebun Baru which aims to improve participants' Arabic language skills. The existence of a program like this course provides a positive atmosphere in learning Arabic in formal classes. The existence of the Arabic Camp program strengthens the achievement of learning Arabic subjects according to the formal curriculum. The ability of the participants who entered the seventh grade for the first time varied. This diversity is due to the different schools/madrasas of origin. After the Arabic Camp program, participants who originally had Arabic language skills, these participants became more confident when studying Arabic subjects